FRI0388 Long-term treatment with rituximab in systemic sclerosis patients: update of our clinical experience. (15th June 2017) - Lumetti, F; Colaci, M; Esposito, C; Cocchiara, E; Vacchi, C; Spinella, A; Tiengo, G; Giuggioli, D; Ferri, C
Abstract : Background: Systemic sclerosis (SSc) is an immune-mediated disorder characterized by abnormal fibrosis and diffuse microangiopathy with skin and internal organ involvement. The treatment of SSc represents a great clinical challenge because of the complex disease pathogenesis including vascular, fibrotic, and immune T- and B-lymphocyte-mediated alterations. Therefore, SSc should be treated by combined or sequential therapies according to prevalent clinico-pathogenetic phenotypes. Some preliminary data suggest that rituximab (RTX) may be usefully employed in SSc patients. Objectives: The present study aimed to evaluate the efficacy of RTX in our SSc patients' series as well as the long-term effects of this treatment. Methods: A series of 15 SSc patients (M/F 6/9, mean age 52.7±17.9SD years, mean disease duration 10.3±7.1SD years, L/D cutaneous subsets 5/10) were treated with one or more cycles of RTX (4 weekly infusions of 375 mg/m 2 ). In all patients RTX was repeated every 6 months for a total of 2–6 cycles. Patients' clinical-serological evaluation, including the self-evaluation of quality of life by means of HAQ and visual analogical scale (VAS) assessment, was performed every 6 months for a mean follow-up period of 42±24SD months. Results: After the first 6 months following RTX treatment the extent of skin sclerosis measured with modified Rodnan skin score (mRSS) significantly improved (from 17.3±10.4 to 13.4±7.6; p<.01), and remained stable at the end of the follow-up (13.3±8.1; p=.009). The usefulness of RTX on skin sclerosis was more evident in patients with diffuse cutaneous SSc (n=10) showing a significant decrease of mRSS after the first 6 months (from 24.2±5.1 to 18.1±4.7; p=.006) and at the end of the follow-up period (18.0±6.0; p=.005). Similarly, a valuable improvement of other cutaneous manifestations, namely hypermelanosis (12/12 pts), pruritus (11/13 pts), and calcinosis (3/6 pts) was observed. Moreover, arthritis revealed particularly responsive to RTX treatment leading to a clear-cut reduction of swollen and tender joints in 12/13 patients; while lung fibrosis detected in 12/15 remained stable during the entire follow-up.These positive clinical changes were mirrored by the subjective improvement of patients' well being in all cases (HAQ from 1.45±0.49 to 0.98±0.38, VAS from 64.5±18.5 to 37.5±8.6). Finally, no significant side effects were observed. Conclusions: The present study reinforces the previous trials showing the usefulness of RTX in the management of SSc patients, along with its good safety profile. The specific therapeutical activity of RTX, able to down-regulate the B-cell over expression, might explain its beneficial effects on some SSc clinical manifestations; in particular the improvement of both skin sclerosis and articular involvement, along with the possible stabilization of lung fibrosis. Disclosure of Interest: None declared